Analyzing the U.S. dairy and nondairy milk markets: three essays on consumer demand, product separability, labeling, and welfare - Ghazaryan, Armen, author; Bonanno, Alessandro, advisor; Thilmany McFadden, Dawn, committee member; Costanigro, Marco, committee member; Bellows, Laura, committee member (Colorado State University. Libraries, 2020)
This dissertation is comprised of three main chapters, presenting empirical analyses of different aspects of the U.S. dairy and nondairy milk markets. In Chapter 2, two different empirical analyses are performed: 1) tests for weak separability in an Exact Affine Stone Index (EASI) milk demand system that includes dairy and nondairy milks; 2) tests of aggregability of dairy and nondairy milk products in the context of demand analysis by implementing an empirical test based on the Generalized Composite Commodity Theorem (GCCT). We use a revealed-preference approach and point-of-sale weekly scanner data of dairy and nondairy milk products' sales from 2012 to 2017. To our knowledge, this is the first study to implement weak separability tests for the linear-approximate EASI model. The goal of Chapter 3 is to estimate how much consumers value the "milk" label on nondairy milks, and, as a result, how much producers of nondairy milks may be seeking to capitalize on consumers' preference through the use of dairy terminology. The analysis performed in Chapter 3 uses one year of monthly point-of-sale scanner data from 2013 to analyze the demand for dairy and nondairy milks using a random coefficients logit model. Additionally, we estimate the welfare implications of the presence of the "milk" label on nondairy milks for consumers as well as dairy and nondairy milk producers. In Chapter 4, we first use the concept of diversion ratios to assess whether strategic price changes by nondairy milk producers can constitute a threat for dairy milk producers (in terms of market shares) and vice versa. Then, we assess how changes in the market definition of nondairy milks may affect the milk market.
Keywords: demand analysis; nondairy milk; dairy alternative beverages; welfare; labeling